2017
DOI: 10.1016/j.mrrev.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

HPV entry into cells

Abstract: Human papillomavirus (HPV) is a sexually transmitted virus responsible for the development of cervical cancer, anal cancer, head and throat cancers, as well as genital area warts. A major focus of current HPV research is on preventing the virus from entering a cell and transferring its genetic material to the nucleus, thus potentially preventing the development of cancer. Although the available HPV vaccines are extremely successful, approximately 15 additional cancer-causing HPVs have been identified that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 103 publications
1
84
0
3
Order By: Relevance
“…HPV infection occurs following microabrasions exposing the basement membrane and polarized adherent basal keratinocytes to HPV 34,35 . Following interactions of the viral capsid proteins with ECM, apical cellular proteins, and receptors, the HPV capsid is internalized and undergoes retrograde endosomal trafficking toward the nucleus, where it resides within vesicles until breakdown of the nuclear envelope 36 .…”
Section: Discussionmentioning
confidence: 99%
“…HPV infection occurs following microabrasions exposing the basement membrane and polarized adherent basal keratinocytes to HPV 34,35 . Following interactions of the viral capsid proteins with ECM, apical cellular proteins, and receptors, the HPV capsid is internalized and undergoes retrograde endosomal trafficking toward the nucleus, where it resides within vesicles until breakdown of the nuclear envelope 36 .…”
Section: Discussionmentioning
confidence: 99%
“…HPV infectious entry involves a complex series of steps, including the attachment of virus to the extracellular matrix, the structural remodelling of the virion, receptor attachment, endocytic uptake, intracellular trafficking through the endosomal compartment, uncoating, and the recruitment of different components of the cellular transport machinery to ensure delivery of the incoming viral genomes to the nucleus through the trans-Golgi network (25)(26)(27). However, no studies have been performed to investigate whether potential phosphorylation of the HPV capsid proteins can play any roles in any of these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Interactions of the viral capsid proteins with cellular components play an important role in papillomavirus infectious entry (25)(26)(27). Intracellular processing of the viral capsid is dependent on a number of different host factors, such as furin (13), cyclophilin (16), and gamma-secretase (21,(28)(29)(30), among others.…”
mentioning
confidence: 99%
“…During HR-HPV infection, the virus binds to the receptors on the target cell surface, resulting in its internalization, and subsequently, the viral DNA is released and transported to the cell nucleus (45,64). After the viral DNA is integrated, it synthesizes the E6 and E7 oncoproteins that promote proliferation for TP53 degradation by E6 and pRB degradation by E7; it has been observed that the degradation of pRb leads to the overexpression of OCT3/4 and that the degradation of p53 leads to an increase in the expression of NANOG (65,66), and it is well known that NANOG can directly bind to the OCT3/4 gene promoter to induce its expression (67-69).…”
Section: Oct3/4 and E6 And E7 Oncoproteinsmentioning
confidence: 99%